Women’s knowledge and practices of modern contraceptives in rural Jammu - Sharma, Suksham; Dogra, Anju; Bavoria, Shalli (International Journal Of Community Medicine And Public Health, 2022)
Background: India was the first country in the world to adapt a national population control program in 1952. So, it is important for couples and society as a whole to understand and adopt the methods of family planning. Use of contraceptives can prevent at least 25% of all maternal deaths by preventing unintended pregnancies and unsafe abortions and also protect against sexually transmitted infections. Methods: A cross-sectional study was conducted in the women of the reproductive age group (15-49 years) in gynae OPD of community health centre of block Bishnah in district Jammu. Results: The study was conducted in 408 women of the reproductive age group. Almost all the women had knowledge of various spacing methods, maximum being for being for oral contraceptive pills (OCPs) (96%), followed by intrauterine contraceptive devices (IUCD) (93.8%) and 90.9% for condoms. However, they had less knowledge about injectable contraceptives (13.9%). Conclusions: Family planning related knowledge was found to be very encouraging with two-third having a positive attitude as well. Main identified reasons for contraceptive defaults were unsustain availability, side-effects, need of a child and family opposition. It is hence, important to improve education of women to overcome barriers to modern contraceptive methods.